2012
DOI: 10.1002/pros.22597
|View full text |Cite
|
Sign up to set email alerts
|

CCL11 (eotaxin‐1): A new diagnostic serum marker for prostate cancer

Abstract: Background The recent recommendation of the U.S. Preventive Services Task Force against PSA-based screening for prostate cancer was based, in part, on the lack of demonstrated diagnostic utility of serum PSA values in the low, but detectable range to successfully predict prostate cancer. Though controversial, this recommendation reinforced the critical need to develop, validate, and determine the utility of other serum and/or urine transcript and protein markers as diagnostic markers for PCa. The studies descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 49 publications
2
49
2
Order By: Relevance
“…Since chemokines are associated with more aggressive disease and poor prognosis in diverse malignancies, and significant modifications of chemokines repertoire occurred during tumorigenesis of prostate cancer, chemokine system may represent a promising diagnostic biomarker that may guide strategies to improve prostate cancer therapy. Recently, pilot studies have been driven to investigate the diagnostic relevance of chemokines in prostate cancer and CCL2, CCL18, CCL11, and CXCL8 have been found to be new potential serum biomarkers [108][109][110][111][112]. For example, the elevated serum levels of both CCL11 and CCL18 in prostate cancer patients than those in benign hyperplasia patients may provide a useful diagnostic tool to help distinguish between the two pathological conditions among men demonstrating low, but detectable, serum PSA values [109,110].…”
Section: Chemokines and Prostate Cancermentioning
confidence: 99%
“…Since chemokines are associated with more aggressive disease and poor prognosis in diverse malignancies, and significant modifications of chemokines repertoire occurred during tumorigenesis of prostate cancer, chemokine system may represent a promising diagnostic biomarker that may guide strategies to improve prostate cancer therapy. Recently, pilot studies have been driven to investigate the diagnostic relevance of chemokines in prostate cancer and CCL2, CCL18, CCL11, and CXCL8 have been found to be new potential serum biomarkers [108][109][110][111][112]. For example, the elevated serum levels of both CCL11 and CCL18 in prostate cancer patients than those in benign hyperplasia patients may provide a useful diagnostic tool to help distinguish between the two pathological conditions among men demonstrating low, but detectable, serum PSA values [109,110].…”
Section: Chemokines and Prostate Cancermentioning
confidence: 99%
“…CCL11 is known as a chemotactic factor that binds to the CCR3 receptor, activates the mitogen-activated protein kinase pathway, and stimulates cellular invasion by regulating the expression of matrix metalloproteinase-3 [13]. CCL11 has been proposed by two research groups to be a serum marker for PCa; Agarwal et al [3] suggested that serum CCL11 may be a useful diagnostic tool to help distinguish between prostatic enlargement and PCa among men demonstrating low, but detectable, serum PSA value; Heidegger et al [4] reported that CCL11 may serve as a diagnostic marker to distinguish between disease-free prostate condition and PCa.…”
Section: Discussionmentioning
confidence: 99%
“…PSA screening is associated with a significant decline in prostate cancerspecific mortality in the US over the past two decades [15,16], although the recommendation by the United States Preventive Services Task Force does imply that low serum PSA values alone do not reliably predict clinically significant prostate tumors. Therefore, there is a critical need to develop, validate, and determine the utility of other serum transcripts and protein markers as diagnostic markers for PCa [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In prostate cancer, CCL11 acts via CCR3 to accelerate tumor invasion and migration, which are dependent on ERK1/2 activation and MMP3 expression (Zhu et al, 2014). Accordingly, serum CCL11 levels are elevated in prostate cancer (Agarwal et al, 2013). CCL11 also induces phosphorylation of ERK1/2, MEK1, and STAT3 in ovarian carcinoma and stimulates αCD28 mAbs + MDSC harvested from CpG-treated KC mice (5:1 T cell/MDSC ratio).…”
Section: Discussionmentioning
confidence: 99%